Presence of Coxiella burnetii DNA in the Environment of the United States, 2006 to 2008 - Kersh, Gilbert J. (American Society for Microbiology (ASM), 2010)
Coxiella burnetii is an obligate intracellular bacterium that causes the zoonotic disease Q fever. Because C. burnetii is highly infectious, can survive under a variety of environmental conditions, and has been weaponized in the past, it is classified as a select agent and is considered a potential bioweapon. The agent is known to be present in domestic livestock and in wild animal populations, but the background levels of C. burnetii in the environment have not been reported. To better understand the amount of C. burnetii present in the environment of the United States, more than 1,600 environmental samples were collected from six geographically diverse parts of the United States in the years 2006 to 2008. DNA was purified from these samples, and the presence of C. burnetii DNA was evaluated by quantitative PCR of the IS1111 repetitive element. Overall, 23.8% of the samples were positive for C. burnetii DNA. The prevalence in the different states ranged from 6 to 44%. C. burnetii DNA was detected in locations with livestock and also in locations with primarily human activity (post offices, stores, schools, etc.). This study demonstrates that C. burnetii is fairly common in the environment in the United States, and any analysis of C. burnetii after a suspected intentional release should be interpreted in light of these background levels. It also suggests that human exposure to C. burnetii may be more common than what is suggested by the number of reported cases of Q fever.